ELNAIS: A collaborative network on Aquatic Alien Species in Hellas (Greece) - Zenetos, A.; Arianoutsou, M.; Bazos, I.; Balopoulou, S.; Corsini-Foka, M.; Dimiza, M.; Drakopoulou, P.; Katsanevakis, S.; Kondylatos, G.; Koutsikos, N.; Kytinou, E.; Lefkaditou, E.; et al. (Management of Biological Invasions, 2015)
ELNAIS is a dynamic online information platform aiming to collect and report spatial information on Aquatic Alien Species in Greek waters. It covers freshwater, marine and estuarine waters, including not only established aliens but also casual records and cryptogenic species. The ELNAIS system includes: News, List of Greek experts, Literature of findings in Greece, List of species with information on their first introduction date and source as well as photos and distribution maps. Data providers are the scientific community (publications, grey literature, and databases) as well as citizen scientists. ELNAIS provides a useful tool towards national obligations and commitments under both the European and global frameworks in respect to Non Indigenous Species (CBD, WFD, MSFD).